Figure 6 in Somatic musculature of Tardigrada: phylogenetic signal and metameric patterns - Marchioro, Trevor; Rebecchi, Lorena; Cesari, Michele; Hansen, Jesper Guldberg; Viotti, Giulia; Guidetti, Roberto (Zenodo, 2013)
Figure 6. Schematic representations of musculature. A, Echiniscus testudo; B, Milnesium cf. tardigradum; C, Acutuncus antarcticus. Muscles of the ventral group are in red, their nodes are marked by hexagons; muscles of the lateral group are in blue, their attachment points and nodes are marked by squares; muscles of the dorsal group are in green, their attachment points and nodes are marked by circles. Letters and numbers identify the muscle attachment points (see text). Ph, pharynx. : Published as part of Marchioro, Trevor, Rebecchi, Lorena, Cesari, Michele, Hansen, Jesper Guldberg, Viotti, Giulia & Guidetti, Roberto, 2013, Somatic musculature of Tardigrada: phylogenetic signal and metameric patterns, pp. 580-603 in Zoological Journal of the Linnean Society 169 (3) on page 589, DOI: 10.1111/zoj.12079, http://zenodo.org/record/5291175